2008
DOI: 10.1139/h08-051
|View full text |Cite
|
Sign up to set email alerts
|

A 26 year physiological description of a National Hockey League team

Abstract: The primary purpose of this investigation was to examine the physiological profile of a National Hockey League (NHL) team over a period of 26 years. All measurements were made at a similar time of year (pre-season) in 703 male (mean age +/- SD = 24 +/- 4 y) hockey players. The data were analyzed across years, between positions (defensemen, forwards, and goaltenders), and between what were deemed successful and non-successful years using a combination of points acquired during the season and play-off success. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 13 publications
8
82
2
1
Order By: Relevance
“…Analysis of the obtained results on aerobic and anaerobic capacity revealed that they were similar to the results obtained by other researchers worldwide [3,5,18,19].…”
Section: Resultssupporting
confidence: 88%
“…Analysis of the obtained results on aerobic and anaerobic capacity revealed that they were similar to the results obtained by other researchers worldwide [3,5,18,19].…”
Section: Resultssupporting
confidence: 88%
“…The game is characterised by irregular changes between high and low intensity activities over very short periods of time (up to 10 s) with high-impact body contact. Low intensity activities are related to the recovery processes (Balsom, Seger, Sjodin, & Ekblom, 1992;Quinney et al, 2008;Vescovi, Murray, & VanHeest, 2006). Each on-ice shift last between 30 and 80 s interspersed with 2 to 5 min of recovery between shifts (Arnett, 1996;Quinney et al, *Address for correspondence: Karel Hůlka, Department of Sports, Faculty of Physical Culture, Palacký University, tř.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the volume of exercise shows that training of young football players focuses especially on the development of aerobic endurance and playing skills. In young ice hockey players this particularly includes the development of a complex of strength, anaerobic capacity and agility (Brocherie et al, 2005;Burr et al, 2008;Hoff et al, 2005;Psotta et al, 2006;Quinney et al, 2008;Sigmund, Kohn, Sigmundová, in press;Stølen et al, 2005;Vescovi et al, 2006). With regard to the difference in the fitness training, one could assume different changes in selected morphological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the players use 70-80% of their maximum aerobic power; there are differences due to various skating levels of individual players. Physiological demands on the players vary depending on the position of each player in the team (goalkeeper, defender, forward) and their playing style (Brocherie et al, 2005;Hoff et al, 2005;Manners, 2004;Montgomery, 2006;Quinney et al, 2008;Sigmund, Kohn, Sigmundová, in press;Vescovi et al, 2006). The facts mentioned above have an effect on the structure of sports training with regard to sports specialization.…”
Section: Introductionmentioning
confidence: 99%